Cambridge checkpoint lower secondary science workbook grade 8 Based on SNC 2022 - Riley, Peter D. (Hodder education: London, 2023)
The Cambridge Checkpoint Lower Secondary Science Workbook Grade 8 complements the student$1 (Bs book by reinforcing key concepts in biology, chemistry, and physics. It includes practical exercises, problem-solving tasks, and critical thinking activities to deepen understanding and enhance scientific skills. The workbook focuses on applying knowledge through hands-on practice and assessments aligned with the curriculum.s
Keywords: General science - Textbook